Chemopreventive potential of water and methanolic extracts of Clinacanthus nutans (Burm.f.) Lindau on colon cancer in vitro and in vivo - Kura, Mariamu Nyako (2015)
Chemoprevention is a promising approach in controlling the occurrence of colorectal cancer (CRC). In this study the effects of extracts of Clinacanthus nutans (Cn) on colorectal cancer in vitro and in vivo was investigated. Cn Leaf and stem were extracted using sonication. Cytotoxicity testing of the extracts on the human colon adenocarcinoma cell line HT- 29 was determined. For the in vivo study, male Sprague Dawley rats were randomly assigned to six groups. Rats in treatment groups were administered 100mg/kg 1, 2- dimethylhydrazine (DMH) by gavage twice in the first week. The extracts were administered for eight weeks. After sacrifice, full blood count and histological analysis of the colons and livers of experimental animals was then carried out. The extracts were also analyzed qualitatively for the presence of certain phytochemicals. IC50 values of 771.28±0.35μg/ml, 911.8±0.06μg/ml and 622.63±0.2μg/ml were observed for the water, hot water and methanolic extracts of the leaves of Cn after 72h treatment respectively. The number of aberrant crypt foci and crypt multiplicity significantly decreased in the colons of rats in the 500mg/kg water extract treated group. The 500mg/kg water extract also significantly decreased hepatic steatosis and significantly increased mRNA expression of SOD1antioxidant gene in the liver of rats. The extracts induced a certain amount of toxicity in blood of treated rats (anemia, decreased total White blood cell counts, decreased thrombocyte counts and decreased monocyte counts). Phytochemical screening of the extracts of also revealed the presence of saponins, tannins, alkaloids, flavonoids, carbohydrates, phenols and diterpenes. Though it induced toxicity in the blood of treated rats, the water extract of the leaf showed the most chemopreventive potential among the 12 extracts of Clinacanthus nutans studied therefore this merits the further study of this extract for clinical trials.